Municipality-Level Source Apportionment of PM2.5Concentrations based on the CAPSS 2016: (V) Ulsan - Kang, Yoon Hee; You, Seunghee; Son, Kyuwon; Kim, Eunhye; Bae, Minah; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The annual mean PM2.5concentration in Ulsan, the largest industrial city in South Korea, still does not meet the national ambient air quality standard (15 μg/m3) while the PM2.5concentrations have recently shown a decreasing trend. In this study, we identified the major contributors to PM2.5concentrations in Ulsan for the year of 2016 using the Comprehensive Air quality Model with eXtensions with Particulate Source Apportionment Technology (CAMx-PSAT). The foreign and domestic contributions to the annual PM2.5concentration in Ulsan were 11.3 μg/m3, 11.6 μg/m3, respectively. The average of selfcontribution was 6.8 μg/m3in Ulsan, while Nam-gu where the Ulsan·Mipo national industrial complex are located had the highest self-contribution (13.0 μg/m3, 75% of domestic contributions) among five local authorities in Ulsan. The contributions of Gyeongbuk, one of the neighboring provinces, to the annual mean PM2.5in Ulsan was the highest (1.4 μg/m3) for the year, followed by Gyeongnam (0.6 μg/m3), Chungnam (0.5 μg/m3), Busan (0.4 μg/m3), and Daegu (0.2 μg/m3). It was confirmed that the contributions were affected by prevailing winds in and around Ulsan. During the warm season (April to July), the selfcontribution was 2.5 times higher than the neighboring provincial contribution even though the PM2.5contributions of Busan and Gyeongnam, locating in the south and west of Ulsan, have increased during the warm season. For the rest of the year, the self- and neighboring provincial contributions were similar to 5.1 and 4.8 μg/m3, respectively. Note that uncertainties in the emissions inventory used in this study (i.e., Clean Air Policy Support System 2016) have clearly led to the over-predictions of the PM2.5and SO2in Nam-gu, Ulsan. It is, therefore, a prerequisite to have the local emissions that can explain the current air pollution in the area prior to developing a comprehensive air quality improvement plan.
Keywords: Industrial city; Local winds; PM2.5; Self-contribution; Ulsan